Thyroid Profile of Childhood Tuberculosis Treated with Anti Tuberculosis Drug During Intensive Phase - Moh Syarofil Anam; Mahmudah Mahmudah; Ferdy K Cayami; Maria Mexitalia; Magdalena Sidhartani; Hertanto Wahyu Subagio; Agustini Utari (Journal of Biomedicine and Translational Research, 2022)
Background: Tuberculosis (TB) is an infectious disease caused by Mycobacterium tuberculosis.  The incidence is  10 % in children. Tuberculosis has high morbidity and mortality which needs adequate treatment. The side effects of FDC is thyroid hormone dysfunction which can interfere children's quality of life. However, research about the effect of FDC therapy on thyroid hormone profile in children with TB are very limited. Objective: To determine the effect of anti-tuberculosis drug treatment on thyroid hormone profile in paediatric tuberculosis. Methods: A one group pretest-posttest design study of 50 patients was conducted at the Semarang Health Center for the period January 2021-June 2021. Thyroid function tests of TSH, FT4 and T3, in TB children were measured before FDC therapy and 2 months after administration. The data were analysed descriptively and a comparative test was performed using SPSS 25.Results: There were no significant differences in TSH, FT4 and T3 serum levels before FDC therapy and 2 months of FDC administration. Thyroid hormone levels before treatment and 2 months after administration of FDC, respectively, euthyroid in 44 vs 42 patients.Conclusion: Two months of tuberculosis treatment in children decreased the serum FT4 and T3 level but no changes in the serum TSH level before and after the treatment.